Pre-marital sex among Malay adolescents: counseling interventions - Mansor, Norwati (s.n, 2013)

(untitled)
The issue of premarital sex among young adolescents in Malaysia has received a great deal of attention from parent, educators, religious leaders, the government and other concerned parties in recent years because of its implications with problems particularly the increasing incidence of unwanted out of wedlock pregnancies and baby abandonment among this group of people. If in 2009, the welfare department reported handling 131 cases of teenage pregnancies, in 2010, only by April, the department has already received 111 pregnant girls at its rehabilitation centre for out of wedlock pregnant adolescents (The Star, June 26,2010). The main purpose of the study is to investigate the reason of the engagement of school-age Malay female adolescents in premarital sex. It also seeks to examine the role of religion in influencing the involvement of Malay female adolescents in premarital sex as well as how the adolescents practice Islam in their daily lives. This is to enlighten concerned parties on the role of the Islamic religion in relation to the involvement of the Malay Muslim adolescents in premarital sex